Genome-wide DNA-binding specificity of PIL5, an Arabidopsis basic Helix-Loop-Helix (bHLH) transcription factor. (11th October 2010) - Kang, Hyojin; Oh, Eunkyoo; Choi, Giltsu; Lee, Doheon
PIL5 is a member of the basic Helix-Loop-Helix (bHLH) transcription factor superfamily. We previously showed that PIL5 binds to the G-box (CACGTG) motif with high affinity. However, since there are many randomly matched G-box motifs throughout the genome, other factors must account for the in-vivo PIL5 binding specificity. In this study, we investigated if in-vivo PIL5 binding sites can be explained by any other attributes extracted from various sources. Our results showed that PIL5 binding sites can be explained by attributes such as neighbouring motif composition, nucleosome density, DNA methylation and distance from transcription start site in addition to G-box.